Finite element analysis of Epoxy/E-Glass composite material based mono leaf spring for light weight vehicle - Bhandari, Anil Mani; Neupane, Sudan; Adhikari, Ushan; Risal, Sunil (Journal of Innovations in Engineering Education, 2021)
A great deal of work is put into decreasing the fuel consumption of automotive vehicles, which may be accomplished by reducing the bulk of the vehicles. One component that may be explored is the leaf spring, which is extensively utilized in many sorts of cars, including electric ones. For the leaf spring, four distinct materials are considered: standard steel, Epoxy/E-Glass UD composite, Epoxy/E-Glass Wet composite, and Epoxy/S-Glass UD composite. The FEA study executed with the help of the ANSYS finite element code. Firstly, the 3-D model of the leaf spring with different thickness varying from 15mm to 65mm is designed using SolidWorks software which is then imported to the ANSYS software for the static analysis. Along with this, the finite element analysis under full load on 3-D composite multi leaf spring model is executed using ANSYS 2020 R1 by taking three different materials and then the result for the different static behaviour of the leaf spring are compared for all the materials assigned. In this paper we describe design and analysis of composite leaf spring. The leaf spring model used for this purpose is a rear leaf spring used in MAHINDRA “MODEL-COMMANDER 650 DI”. When compared to traditional steel, the mass of hybrid composite material is 62% lower. Hybrid composite materials have 36% lower equivalent (Von-Mises) stress than steel. Utlimately, the hybrid composite material may be employed as a leaf spring, decreasing the total weight of automobiles.